2020
DOI: 10.1111/nph.16563
|View full text |Cite
|
Sign up to set email alerts
|

Exploring folds, evolution and host interactions: understanding effector structure/function in disease and immunity

Abstract: Summary Over the past decade, tremendous progress has been made in plant pathology, broadening our understanding of how pathogens colonize their hosts. To manipulate host cell physiology and subvert plant immune responses, pathogens secrete an array of effector proteins. A co‐evolutionary arms‐race drives the pathogen to constantly reinvent its effector repertoire to undermine plant immunity. In turn, hosts develop novel immune receptors to maintain effector recognition and mount defences. Understanding how ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
29
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 63 publications
0
29
1
Order By: Relevance
“…Diffraction data was collected at Diamond Light Source, i03 beamline, under proposal mx18565. The data were scaled and merged by Aimless in the CCP4i2 software package (2). The AvrRps4 C /RRS1 WRKY complex structure was solved by molecular replacement using PHASER (3) with the structures of AvrRps4 C (PDB ID: 4B6X) and PopP2/RRS1 WRKY (PDB ID: 5W3X) as search models.…”
Section: Supplementary Informationmentioning
confidence: 99%
See 1 more Smart Citation
“…Diffraction data was collected at Diamond Light Source, i03 beamline, under proposal mx18565. The data were scaled and merged by Aimless in the CCP4i2 software package (2). The AvrRps4 C /RRS1 WRKY complex structure was solved by molecular replacement using PHASER (3) with the structures of AvrRps4 C (PDB ID: 4B6X) and PopP2/RRS1 WRKY (PDB ID: 5W3X) as search models.…”
Section: Supplementary Informationmentioning
confidence: 99%
“…Plants co-evolve with their pathogens, resulting in extensive genetic variation in host immune receptor and pathogen virulence factor (effector) repertoires (1). To enable host colonization, pathogenic microbes deliver effector proteins into host cells that suppress host immune responses and elevate host susceptibility by manipulating host physiology (2, 3). Plants have evolved surveillance mechanisms to detect and then activate defenses that combat pathogens, and detect host-translocated effectors via nucleotide-binding leucine-rich repeat receptors (NLRs) (4).…”
Section: Introductionmentioning
confidence: 99%
“…Sequence analyses revealed that Avh241 contains two conserved WY motifs, which have been identified in many RxLR effectors (Yu et al, 2012). Although the sequence similarity of these effectors is low, they display a conserved fold buried within the core of the helical bundle (Win et al, 2012; Mukhi et al, 2020). Recently, the crystal structure of Avh240 revealed a duplicated WY domain with a novel assembly model (Guo et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…The successful loosening of the cell wall further causes the transfer of various apoplastic, cytoplasmic effectors as well as virulence determinants that suppress the immunity of the host in numerous ways. Several novel mechanisms have been utilized by pathogens that have been highlighted by recent studies, such as suppressing RNA interference, targeting various cellular organelles of host plants, and maintaining conserved fold in the novel effectors to perform a conserved molecular function(de Guillen et al, 2019; Jaswal et al, 2020; Mukhi et al, 2020; Xu et al, 2019; Yin et al, 2019).…”
Section: Introductionmentioning
confidence: 99%